1982
DOI: 10.1111/j.1939-0025.1982.tb02686.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociopsychological determinants of women's breast-feeding behavior: A replication and extension.

Abstract: Women's birth experience, studied in two time periods, had negligible impuct on their persistence in breast-feeding, nor did early postpartum experience, type of feeding regimen, or timing of solid food introduction emerge as significunt correlates. Women's prenatal intentions were the strongest predictor of breast-feeding success in the first month, and the mother's own history of having been breast-fed us an infant appears to be a predisposing factor. The influence of socioeconomic factors and childbirth pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…The hypothesis regardmg prenatal intent was only partially supported Intended duration of breastfeedmg was found to be a discnmmating factor supportmg previous research (Buxton et al 1991, Conel & Murphy 1988, Entwisle et al 1982, Loughlin et al 1985, O'Campo et al 1992, however, commitment score and total confidence score were not found to be significant…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The hypothesis regardmg prenatal intent was only partially supported Intended duration of breastfeedmg was found to be a discnmmating factor supportmg previous research (Buxton et al 1991, Conel & Murphy 1988, Entwisle et al 1982, Loughlin et al 1985, O'Campo et al 1992, however, commitment score and total confidence score were not found to be significant…”
Section: Discussionsupporting
confidence: 83%
“…The failure of confidence as a predictor of breastfeeding duration supports the importance of considermg pnmiparas as a separate population Only Entwisle et al (1982) completed their study with pnmiparas, and confidence was not mcluded as a component m their definition of prenatal intent Others (Buxton et al 1991, Coriel & Murphy 1988, Loughlm et al 1985, O'Campo et al 1992 had subject pools combining both pnmiparas and multiparas In the present study, while confidence m ability to overcome problems was significantly related to planned duration of feeding, confidence was not itself a predictor of feedmg at 12 weeks It appears that while confidence based on a previous expenence may predict success it is not an indicator of breastfeedmg duration for those having their first child Having a high commitment level to carry through with the breastfeeding decision has only been measured in relation to breastfeeding duration by Buxton et al (1991) The fact that the duration of breastfeeding measured m this study was only 1 week and that they did not exclusively measure pnmiparas could account for the different result In the present study, only two women were not breastfeeding after 1 week Identifying those who establish breastfeeding but then partly or totally abandon it with 12 Table 3 Means and standards deviations of significant predictor variables of breastfeeding status at 12 weeks Intended duration and atUtude to formula are rated on a six-point scale Higher scores indicate an intention to breast feed for a longer period and more negative attitudes to formula feeding Tuning of decision to breastfeed, hours m care of others and education are rated on a four-point scale, with higher values mdicating higher levels of education, later timing of decision to feed and longer hours in the care of others Timing of first breastfeed is rated on a three-point scale, with higher values indicating more hours after birth before fixst feed weeks of birth appears related not to mothers' confidence but to when she decided on breastfeeding, how long she planned to feed for and how negative she felt about the use of fonnula While over 90% of subjects planned to feed beyond 4 months, abandoning or reducing breastfeeding earlier may be less of an attitude shift to those who planned to put their baby on fonnula at some stage rather than feedmg until the baby could be weaned on cows milk…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the decision-making model, prenatal intent was a strong predictor of breastfeeding initiation. This finding concurs with previous studies (Entwisle et al, 1982;Coreil and Murphy, 1988). Less than one-quarter of the women had decided how to feed their babies before pregnancy.…”
Section: The Breastfeeding Decision-making Modelsupporting
confidence: 95%
“…Only after the contingent variables are known, can health professionals plan a course of action to stimulate breastfeeding. Studies have repeatedly shown that the length of time for which a woman intends to breast feed is a very good predictor of her behaviour (Becke & Garvis 1982; Entewisle et al 1982; Richardson & Champion 1992). Until actual breast feeding duration is investigated, research concerning the variables associated with intentions can help identify women most at risk for early abandonment of breast feeding.…”
Section: Introductionmentioning
confidence: 99%